Undermining competition, undermining markets? Implications of Big Tech and digital personal data for competition policy - Kean Birch; ‘Damola Adediji (Big Data & Society, 2025)
Many countries and jurisdictions are reforming their competition policies in response to growing political and public concerns about market concentration, especially when it comes to the market power of Big Tech firms. A particular concern is the new dynamics in market competition resulting from the rise of digital personal data as the key resource or asset underpinning our economies. Our aim in this paper is to examine the competition policy investigations, proposals, and reforms emerging around the world in order to analyse the policy implications of digital personal data to market competition regimes. Our methodological approach entailed an analysis of policy materials (written in English) produced in various jurisdictions or by international institutions dealing with competition policy. We identified the underlying policy themes, concerns, and processes across these different jurisdictions and institutions in order to understand their concerns about how Big Tech and personal data affect competition and competition policy.